2007
DOI: 10.1111/j.1528-1167.2007.01376.x
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual and language functions in children of mothers with epilepsy

Abstract: SUMMARYPurpose: To compare the intellectual and language functions of children of mothers with epilepsy (CME) with that of controls matched for age and socioeconomic status. Methods: Cases were CME, aged six years or more (n = 71), drawn from a prospective cohort in the Kerala Registry of Epilepsy and Pregnancy. Controls were 201 children of parents without epilepsy, matched for age and socioeconomic status. The outcome measures included Indian adaptation of Wechsler Intelligence Scale for children and MLTa lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
53
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 18 publications
5
53
0
1
Order By: Relevance
“…There is growing body of evidence that antenatal exposure to AEDs particularly valproate (VPA) increases the risk for poorer cognitive abilities in children (Adab et al, 2001(Adab et al, , 2004Banach et al, 2010;Gaily et al, 2004;Kantola-Sorsa et al, 2007;Meador et al, 2009;Thomas et al, 2007;Vinten et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…There is growing body of evidence that antenatal exposure to AEDs particularly valproate (VPA) increases the risk for poorer cognitive abilities in children (Adab et al, 2001(Adab et al, , 2004Banach et al, 2010;Gaily et al, 2004;Kantola-Sorsa et al, 2007;Meador et al, 2009;Thomas et al, 2007;Vinten et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…1 Determining the association between exposure to AEDs and child cognitive functioning represents a challenge, and a number of different methodologies have been utilized in its investigation including case studies, [2][3][4] retrospective studies, 5,6 and prospective studies. [7][8][9][10][11][12][13][14][15] Despite limitations, 16 there is growing evidence that exposure to sodium valproate (VPA) in utero is associated with significantly poorer functioning. [10][11][12]15,17 Prospective studies consistently document that VPA is associated with an increase in risk of cognitive impairment in young children, 10,12,15 but any longer-term effects are unlikely to be comprehensively documented until the children studied are of school age, when cognitive development is more stable.…”
mentioning
confidence: 99%
“…[53,54] On the other hand, it must be stressed that concerns regarding the impact of in utero exposure to CBZ on the infant cognitive and motor development were reported by studies that lumped together data coming from different AEDs [55,56] and studies that analyzed the potential neurobehavioral toxicity of single AEDs. [57] Of note, the latter [57] demonstrated that both poor maternal education and low IQ may also compromise the infant developmental outcomes.…”
Section: Antipsychotics (See Table 2)mentioning
confidence: 99%
“…VPA is the psychotropic agent that shows the highest number of reports suggesting that it seriously interferes with several areas of infant development. Reduced IQ scores, [50,57] impaired verbal acquisition, [58,60] increased frequency of maladaptive behavior, [68] as well as global neurodevelopmental delay [61,63] have indeed been reported in children whose mothers took VPA during pregnancy. The risk of VPA-induced neurodevelopmental impairment seems to be dose-dependent, and even more particularly relevant if the drug is used in combination with other AEDs.…”
Section: General Considerationsmentioning
confidence: 99%